2018
DOI: 10.1002/jtr.2215
|View full text |Cite
|
Sign up to set email alerts
|

European rural entrepreneur and tourism‐based diversification: Does national culture matter?

Abstract: Integrated rural tourism assumes a pivotal role in the regeneration of rural areas. The farmer's transition towards rural tourism is influenced by diverse macroeconomic and microeconomic factors. This paper contributes to the debate on tourism-based farm diversification by cross-fertilizing 3 theoretical domains-integrated rural tourism, cultural contexts, and rural entrepreneurship-in order to investigate how national cultural dimensions can influence European rural entrepreneur diversification into the touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…Traditional exploitation of the dehesa based on agriculture and stockbreeding under extensive systems, in addition to its exploitation for hunting, may be vital to the economic development of the spaces in which it predominates, constituting itself as the essential mainstay on which agritourism and even agriecotourism can be based. Indeed it is possible that this activity may contribute to the diversification of agricultural farms [26], although it has been shown that those in charge of the same prefer to establish a clear distinction between the tourist business and the agrolivestock business [27]. Despite everything, there is no clear exploitation of the agritourism development potential of dehesas, which can be attributed both to supply and demand [28]; above all it is taken into account that on this type of farm tourist activities are carried out as part of agricultural exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional exploitation of the dehesa based on agriculture and stockbreeding under extensive systems, in addition to its exploitation for hunting, may be vital to the economic development of the spaces in which it predominates, constituting itself as the essential mainstay on which agritourism and even agriecotourism can be based. Indeed it is possible that this activity may contribute to the diversification of agricultural farms [26], although it has been shown that those in charge of the same prefer to establish a clear distinction between the tourist business and the agrolivestock business [27]. Despite everything, there is no clear exploitation of the agritourism development potential of dehesas, which can be attributed both to supply and demand [28]; above all it is taken into account that on this type of farm tourist activities are carried out as part of agricultural exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, existing studies on women entrepreneurs have shown that the way that women perform as entrepreneurs are significantly impacted by a country's culture and institutional environment (T. M., Joseph and Ul Akram, 2019). Future researchers may also consider conducting comparative and multi-country studies as such studies are currently rare (Calza et al, 2018;Moscardo, 2014).…”
Section: Rural Hospitality and Tourismmentioning
confidence: 99%
“…As seen in the description of the benefits given earlier, researchers in the Global North argue that rural food tourism can reorient agricultural production to domestic consumption, contribute to safeguarding adequate incomes for food producers and promote environmental sustainability which are the qualities for transitions to food sovereignty described by Wiebe, Nettie and Wipf (2011), but the connections are not directly established or examined. There is also limited research regarding how rural tourism stakeholders themselves conceptualize concepts related to sustainability [61] and by extension, food sovereignty. Food sovereignty aspirations need to incorporate inclusive, equitable and environmentally sustainable rural economies [8].…”
Section: Food Sovereignty In Rural Food Tourismmentioning
confidence: 99%